TEACHING PRONUNCIATION USING VARIETIES OF PRONUNCIATION TEACHING MATERIALS AND PRACTICES - Andri Purwanto (Scope : Journal of English Language Teaching, 2019)
The objectives of this research are to design a varied materials for teaching pronunciation practices with fun and attractive, to introduce the correct spelling in teaching pronunciation and to encourage students in using English as medium of communication. For these reasons, this study was aimed at exploring the pronunciation teaching materials in Pronunciation Practice module and course syllabus at Indraprasta PGRI University, Jakarta. This reserach tries to measure the output of learning pronunciation with pronunciation practice module which is designed according to Tergujeff’s pronunciation teaching materials: namely phonetic training, reading aloud, listen and repeat, rhyme and verse, rules and instructions, awareness-raising activities, spelling and dictation and ear training; and Celce Murcia’s Pronunciation teaching materials. This confirms that the creative and dynamic use of current pronunciation teaching materials enable the students not only to undergo accuracy-oriented exercises but also fluency-based activities.